Strategi Merespon Hoaks dan Disinformasi: Literasi Digital Sebagai Bagian dari Amar Ma’ruf Nahi Munkar - Najamudin Najamudin; Dwi Muliati; Anggun Duwi Wahyu Ziliwu; Feti Oktaviani; Mutiara Al-Nizar (PT. Student Rihlah Indonesia, 2026)
The rapid circulation of hoaxes and disinformation in the digital age poses significant challenges to social cohesion and moral values, particularly within Muslim communities. This study explores digital literacy as an ethical and religious instrument in implementing the Islamic principle of amar ma’ruf nahi munkar in contemporary cyberspace. Employing a qualitative library research approach, this paper examines classical Islamic sources alongside contemporary studies on digital communication ethics. The findings indicate that digital literacy in Islam transcends technical competence and functions as a form of moral accountability (amanah) rooted in truthfulness (ash-shidq) and responsibility in information dissemination. Practices such as information verification (tabayyun) and corrective engagement in online spaces represent concrete expressions of enjoining good and preventing harm. This study argues that strengthening digital awareness grounded in Islamic ethics is essential for cultivating a healthy, just, and civilized digital public sphere.